Peningkatan Literasi Al-Qur’an dan Pembiasaan Ibadah untuk Penguatan Akhlak Siswa SMA Negeri 6 Sungai Raya - Latif, Abdul; Husni, Muhammad (Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2026)
This Community Service Program (PKM) was conducted at SMA Negeri 6 Sungai Raya with the aim of improving students’ Qur’anic literacy and religious character through the implementation of the Action Learning and Uswah Hasanah (Role Modeling) methods. The Action Learning approach emphasizes students’ active participation in real religious activities, while the Uswah Hasanah method positions teachers as moral exemplars in shaping students’ behavior. The program was carried out through four stages—observation, planning, action, and reflection—integrated with the habituation of religious values. The results indicate a significant improvement in students’ Qur’anic reading and writing skills, worship discipline, and involvement in religious activities. Furthermore, the school environment became more religious, respectful, and collaborative. In conclusion, the synergy between teacher role modeling and student engagement effectively fosters a sustainable character education ecosystem within the school setting.